Consensus recommendations on the use of 18F-FDG PET/CT in lung disease - Delphine L. Chen; Safia Ballout; Laigao Chen; Joseph Cheriyan; Gourab Choudhury; Ana M. Denis-Bacelar; Elise Emond; Kjell Erlandsson; Marie Fisk; Francesco Fraioli; Ashley M. Groves; Roger N. Gunn; et al. (United States, 2025)
Positron emission tomography (PET) with 18F-fluorodeoxyglucose (18F-FDG) has been increasingly applied, predominantly in the research setting, to study drug effects and pulmonary biology and monitor disease progression and treatment outcomes in lung diseases, disorders that interfere with gas exchange through alterations of the pulmonary parenchyma, airways and/or vasculature. To date, however, there are no widely accepted standard acquisition protocols and imaging data analysis methods for pulmonary 18F-FDG PET/CT in these diseases, resulting in disparate approaches. Hence, comparison of data across the literature is challenging. To help harmonize the acquisition and analysis and promote reproducibility, acquisition protocol and analysis method details were collated from seven PET centers. Based on this information and discussions among the authors, the consensus recommendations reported here on patient preparation, choice of dynamic versus static imaging, image reconstruction, and image analysis reporting were reached.